2022
DOI: 10.1093/eurheartj/ehac544.518
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the atrial fibrillation better care pathway in clinically complex patients with atrial fibrillation: a report from the ESC-EHRA EORP-AF General Long-Term Registry

Abstract: Background Clinical complexity is increasingly prevalent among patients with atrial fibrillation (AF). The “Atrial fibrillation Better Care” (ABC) pathway approach has been proposed to streamline a more holistic and integrated approach to AF care; however, there are limited data on its usefulness among clinically complex patients. We analyzed the impact of the ABC pathway in a contemporary cohort of clinically complex AF patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Adherence to just the “B” criterion was not associated with a significant reduction in the risk of the primary outcome of all‐cause death and major adverse cardiovascular events and adherence to the “A and C” criteria had a significantly lower risk compared to the “B and C” criteria. Nonetheless, the number of adverse events progressively decreased as the number of ABC criteria fulfilled increased with the lowest risk in those that were fully ABC adherent, highlighting that each component in the ABC pathway acts synergistically, and a holistic approach to AF management is best to improve patients' outcomes 22,23 . Thus, active measures to reinforce its uptake including education and awareness amongst healthcare professionals is necessary to better patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to just the “B” criterion was not associated with a significant reduction in the risk of the primary outcome of all‐cause death and major adverse cardiovascular events and adherence to the “A and C” criteria had a significantly lower risk compared to the “B and C” criteria. Nonetheless, the number of adverse events progressively decreased as the number of ABC criteria fulfilled increased with the lowest risk in those that were fully ABC adherent, highlighting that each component in the ABC pathway acts synergistically, and a holistic approach to AF management is best to improve patients' outcomes 22,23 . Thus, active measures to reinforce its uptake including education and awareness amongst healthcare professionals is necessary to better patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent international guidelines have recommended its implementation as the cornerstone of the treatment of AF patients, 20 while previous evidence showed the effectiveness of adherence to the approach in improving outcomes of these subjects. 15,18,19 Nevertheless, the optimal treatment of DM clearly represents a key area of intervention for those AF patients who also have DM, and while retrospective studies have demonstrated the efficacy of the ABC pathway in reducing mortality and other adverse events in diabetic patients, 22 there is still uncertainty on whether a mHealth implemented-ABC pathway can improve prognosis of AF-DM patients. 30 The results of our analysis, which focused specifically on the interaction between DM and the effect of the mAFA intervention, show how the implementation of a patient-centred approach to the treatment of AF patients (as encompassed by the mAFA intervention) prescribed at the baseline, lead to a significant increase in the uptake of both anticoagulants (and specifically, NOACs) as well as DM-specific drugs, such as hypoglycaemic agents, and other agents used to treat associated conditions (including statins for dyslipidaemia and calcium-channel blockers for hypertension).…”
Section: Discussionmentioning
confidence: 99%
“…The ABC pathway has been proposed to streamline such a holistic approach, introducing a structured management and optimization of cardiovascular risk factors and comorbidities. Recent international guidelines have recommended its implementation as the cornerstone of the treatment of AF patients, 20 while previous evidence showed the effectiveness of adherence to the approach in improving outcomes of these subjects 15,18,19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations